To drain or not to drain extraperitoneal colorectal anastomosis? A systematic review and meta‐analysis. (February 2014) - Rondelli, F.; Bugiantella, W.; Vedovati, M. C.; Balzarotti, R.; Avenia, N.; Mariani, E.; Agnelli, G.; Becattini, C.
Abstract Aim Anastomotic leakage is the one of the most serious complications in rectal cancer surgery and is associated with high mortality, morbidity and an increased incidence of local recurrence. Although many studies have compared drained and undrained colorectal anastomoses, to date the role of pelvic drainage in extraperitoneal colorectal anastomosis remains undefined. Method We carried out a systematic review of the literature, performing an unrestricted search in MEDLINE and Embase up to 30 October 2012. Reference lists of retrieved articles and review articles were manually searched for other relevant studies. We performed a meta‐analysis of the data currently available on the incidence of extraperitoneal anastomotic leakage, according to the presence or absence of pelvic drainage. Results Overall, eight studies – three randomized clinical trials (RCTs) and five non‐RCTs, comprising a total of 2277 patients – were included in the meta‐analysis. Pelvic drainage was demonstrated to reduce both the leak rate and the rate of reintervention in patients who underwent anterior rectal resection with extraperitoneal colorectal anastomosis (OR = 0.51, 95% CI: 0.36–0.73; and OR = 0.29, 95% CI: 0.18–0.46, respectively) compared with patients without drainage. Overall mortality and infection rates were also evaluated, but a nonsignificant correlation was found with the presence of drainage. Conclusion The meta‐analysis shows that the presence of a pelvic drain reduces the incidence of extraperitoneal colorectal anastomotic leakage and the rate of reintervention after anterior rectal resection.